Flexible, classic and hybrid project management methodologies: advantages and disadvantages - R. K. Nigmatullin; A. G. Dmitriev (Путеводитель предпринимателя, 2023)
The purpose of the work. Nowadays, competition in the market is increasing, which requires organizations to ensure advanced positions for survival. As practice shows, project management method is one of the most demanded and effective management methods. This study aims to examine the efficacy of flexible project management methodologies by contrasting them with conventional methodologies and evaluating the feasibility of integrating them into a hybrid methodology.Methods and Materials: The complex, systemic and comparative approaches are the methodological basis of the study and are mainly based on methods of analysis and systematization.Results: The article describes the analysis of the most demanding flexible project management methods. Each method has its own characteristics and specific criteria for comparison. Moreover, a comparison between flexible and traditional project management approaches was carried out, and the concept of method hybridization was introduced to integrate diverse methodologies at distinct phases of the project.Conclusion: The choice of project management methodology depends on many conditions, such as the complexity of the task, the presence of an experienced team and methodology of its work, the established interaction with the customer, and many other details. Each of them shows its effectiveness under different conditions. Using a hybrid methodology that combines the advantages of different methods allows them to be applied in practice in project management.